2017
DOI: 10.1001/jamaoncol.2016.6744
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Patient Report and Medical Records of Comorbidities

Abstract: Overall, patient reporting provides information similar to medical record abstraction without significant differences by patient race or educational level. Use of patient reports, which are less costly than medical record audits, is a reasonable approach for observational comparative effectiveness research.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
25
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(27 citation statements)
references
References 31 publications
1
25
1
Order By: Relevance
“…However, recent research has shown high agreement between patient self-reported co-morbidities and documentation of these conditions in the medical record. 24 Further, a similar proportion of men had specific co-morbidities based on self-report and electronic medical record. For instance, 44% of men self-reported hypertension and 44% of men had hypertension according to the electronic health record.…”
Section: Discussionmentioning
confidence: 92%
“…However, recent research has shown high agreement between patient self-reported co-morbidities and documentation of these conditions in the medical record. 24 Further, a similar proportion of men had specific co-morbidities based on self-report and electronic medical record. For instance, 44% of men self-reported hypertension and 44% of men had hypertension according to the electronic health record.…”
Section: Discussionmentioning
confidence: 92%
“…Unlike inpatient or hospital discharge records (complete coverage since 1987 58 ) or hospital-based outpatient physician visits (from 2011) which can be retrieved from the Swedish National Patient Register, primary health care data is not tracked on a national level. However, good agreement has been shown between patient-reported comorbidity events and information abstracted from medical records 59 . As with all studies using survey-based data regarding events or experiences from the past, recall error due to time and memory failure is a limitation and can bias our estimates towards the null.…”
Section: Discussionmentioning
confidence: 98%
“…Conflicting evidence regarding the validity of self-reported patient data exists [85, 86]. However, a rigorous recent study concluded that patient reporting provides similar and less costly information compared with medical records [87]. Moreover, comorbidities in hospital medical records are often based on self-report as well, since clinical validation is mostly not feasible.…”
Section: Discussionmentioning
confidence: 99%